2002
DOI: 10.1212/wnl.58.10.1513
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of treatment of primary CNS lymphoma

Abstract: Combination CHT-RT is superior to RT alone. Patients treated with primary CHT containing HD-MTX exhibited improved survival. In these patients, the addition of HD-cytarabine was associated with a better survival, whereas intrathecal CHT was not correlated to outcome. RT may be unnecessary in patients achieving complete remission after receiving HD-MTX-based primary CHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
236
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(245 citation statements)
references
References 34 publications
4
236
1
4
Order By: Relevance
“…Reasons to omit intraventricular therapy in the current trial were a high Ommaya reservoir infection rate and data from retrospective analysis putting into doubt the necessity of intraventricular treatment [4,5]. However, an interim analysis two years after initiation of this trial revealed an unexpectedly high relapse rate with a median response duration of only ten months in responding patients.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Reasons to omit intraventricular therapy in the current trial were a high Ommaya reservoir infection rate and data from retrospective analysis putting into doubt the necessity of intraventricular treatment [4,5]. However, an interim analysis two years after initiation of this trial revealed an unexpectedly high relapse rate with a median response duration of only ten months in responding patients.…”
Section: Discussionmentioning
confidence: 91%
“…Two retrospective analyses addressing the efficacy of intrathecal chemotherapy in PCNSL [4,5] did not find the inclusion of this modality influencing survival. Precise dosage, application route and schedule of intrathecal therapy were not given in a retrospective analysis on 109 out of 363 PCNSL patients treated with heterogeneous regimens including chemotherapy alone, radiotherapy (RT) alone, RT followed by chemotherapy and vice versa [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Reni et al, 1997;Ferreri et al, 2002b). Any chemotherapy regimen without HD-MTX is associated with outcomes no better than those obtained with radiotherapy (RT) alone in these malignancies (Schultz et al, 1996;O'Neill et al, 1999;Mead et al, 2000), while the survival benefit of the addition of other drugs to HD-MTX remains a matter of debate (Reni et al, 2001;Ferreri et al, 2002b). In spite of its central role in PCNSL treatment, the optimal dose, administration schedule, and dose timing of MTX have not been clearly defined.…”
mentioning
confidence: 99%